Testing of Materials and Elements in Civil Engineering (2nd Edition) Volume I - Schabowicz, Krzysztof (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint was proposed and organized as a means to present recent developments in the field of testing of materials and elements in civil engineering. For this reason, the articles highlighted in this editorial relate to different aspects of this topic, from building materials to building structures. The current trend in the development of materials testing in civil engineering is mainly concerned with the detection of flaws and defects in elements and structures using destructive, semidestructive, and nondestructive testing.